Some Aspects of Syeikh Wan Ali Kutan al-Kalantani's Religious Thought in al-Jawhar al-Mawhub wa Munabbihat al-Qulub - Zarif, MMM; Abdullah, WH (Kolej Univ Islam Sultan Azlan Shah, 2024)
Indexed by WOS